Makna Kebahagian pada Guru Daerah 3T (Terdepan, Terluar, Tertinggal) - Agus Dwi Setyawan, Siti Hartinah (Jurnal Fokus Konseling, 2019)
3T areas are the areas most in need of development in all areas. This area is generally in the form of archipelago areas, such as those found in Sumenep regency of eastern Java province that in fact most of its territory in the form of kepuauan. In this 3t area, transportation, communication and education facilities are lacking. Compounded also with the difficulty to mendapakan educators because the duty has a very alarming situation. In this research using qualitative approach with research subject that is teacher which duty in archipelago giligenting Sumenep regency, Madura. This study aims to reveal the meaning of the happiness of local teachers who work in a place that is worrisome and far from the family. Keywords:  Kebahagiaan, Guru Daerah 3T